Sosialisasi Peningkatan Keuntungan Perusahaan Melalui Perbaikan Struktur Modal, Arus Kas Operasi dan Ukuran Perusahaan pada Perumdam Kota Mojokerto - Bambang Ribut Sugiatmono (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The Regional Drinking Water Company (Perumdam) of Mojokerto City as a Regionally-Owned Enterprise (BUMD) has an important role in providing clean water services to the community. However, Perumdam Mojokerto City faces a number of challenges that affect its financial and operational performance, including a less than optimal capital structure, inefficient cash flow management, and limited company scale. The purpose of this study is to identify solutions to increase profits through improvements in capital structure, operating cash flow, and company size. This study uses a qualitative approach. The method of implementing socialization includes planning objectives, schedules, and materials, followed by workshops and seminars, distribution of materials in various formats, evaluation of participant feedback, and documentation that supports the implementation of results to improve the performance of Perumdam Mojokerto City. Socialization at Perumdam Mojokerto City succeeded in providing an understanding of optimizing capital structure, cash flow management, and company expansion, with digital technology solutions, service diversification, and water distribution expansion, as well as continued training support to ensure effective implementation in improving performance and profitability.